Simultaneous probing of nanocrystal (NC)-ligand interaction-induced charge transfer/transport properties at the electron donor (lead selenide NC)/acceptor (zinc oxide) functional interface - Park, Byoungnam; Ko, Hyungduk; Kim, Minkyong (ELSEVIER SCIENCE BV, 2019)
Understanding correlation between interfacial charge transfer and transport at the electron donor/acceptor functional interface has remained elusive despite its impact on the optoelectronic devices because the conventional vertically stacked diode structure as well as energetic and morphological disorder at the interface complicates analysis of the interfacial region. We fabricated a test platform to enable simultaneous probing of charge transfer and transport at the nanocrystal (NC)/metal oxide interface. Using the transmission line method (TLM) in a ZnO/PbSe/ZnO test structure, we measured the ZnO/PbSe contact resistance from which interfacial charge transfer and transport properties can be correlated in relation to interfacial energetics depending on the size of PbSe NC. The interfacial transfer-transport test probe was validated by comparing size dependent energy level offset derived from the contact resistance value with the established trend. Importantly, by altering the chemical nature of the molecules attached to the NC surface, we discovered that charge transport properties including mobility in the PbSe channel away from the interface are extended into the interfacial region, enabling correlation between carrier diffusion and the electrical mobility at the electron donor/acceptor interface. With a very low mobility in the interface region, charge transfer associated with carrier diffusion is suggested to reflect the nature of energetic disordered interfacial region rather than the electrical mobility.
Keywords: QUANTUM-DOT PHOTOVOLTAICS; METAL-ORGANIC INTERFACE; LIGHT-EMITTING-DIODES; SOLAR-CELLS; SEMICONDUCTOR NANOCRYSTALS; RECOMBINATION; INJECTION; TRANSPORT; DEVICES; PHOTODETECTORS